Kompleksitas Permasalahan Hukum Perusahaan serta Perluasan Hukum Usaha melalui Merger, Konsolidasi, dan Akuisisi di Indonesia - Rina Agustina; Winda Zulfahni (Medan Resource Center, 2026)
Business expansion through mergers, consolidations, and acquisitions has become an increasingly important corporate strategy in response to globalization and the growing complexity of commercial activities. Nevertheless, these transactions continue to raise significant legal concerns regarding legal certainty, corporate governance, shareholder protection, and regulatory compliance. This study aims to examine the legal complexities associated with corporate restructuring through mergers, consolidations, and acquisitions in Indonesia, with particular emphasis on their implications for the protection of stakeholders and the effectiveness of the existing legal framework. The research adopts a normative juridical approach by analyzing statutory regulations, legal doctrines, and relevant scholarly literature. The findings indicate that, despite the existence of comprehensive legal provisions governing corporate restructuring, practical implementation remains constrained by inadequate protection of minority shareholders, insufficient transparency, procedural non-compliance, and persistent conflicts of interest. The study argues that strengthening the regulatory framework, enhancing supervisory mechanisms, and reinforcing the principles of good corporate governance are essential to ensuring legal certainty, fairness, and sustainable business expansion within Indonesia's corporate legal system.